Membrane Potential Measurements of Isolated Neurons Using a Voltage-Sensitive Dye - Fairless, Richard; Beck, Andreas; Kravchenko, Mykola; Williams, Sarah K.; Wissenbach, Ulrich; Diem, Ricarda; Cavalié, Adolfo (PLOS ONE, 2013)
The ability to monitor changes in membrane potential is a useful tool for studying neuronal function, but there are only limited options available at present. Here, we have investigated the potential of a commercially available FLIPR membrane potential (FMP) dye, developed originally for high throughput screening using a plate reader, for imaging the membrane potential of cultured cells using an epifluorescence-based single cell imaging system. We found that the properties of the FMP dye make it highly suitable for such imaging since 1) its fluorescence displayed a high signal-to-noise ratio, 2) robust signals meant only minimal exposure times of around 5 ms were necessary, and 3) bidirectional changes in fluorescence were detectable resulting from hyper- or depolarising conditions, reaching equilibrium with a time constant of 4–8 s. Measurements were possible independently of whether membrane potential changes were induced by voltage clamping, or manipulating the ionic distribution of either Na+ or K+. Since FMP behaves as a charged molecule which accumulates in the cytosol, equations based on the Boltzmann distribution were developed determining that the apparent charge of FMP which represents a measure of the voltage sensitivity of the dye, is between −0.62 and −0.72. Finally, we demonstrated that FMP is suitable for use in a variety of neuronal cell types and detects membrane potential changes arising from spontaneous firing of action potentials and through stimulation with a variety of excitatory and inhibitory neurotransmitters.